TECHNOLOGIES OF RECOGNITION OF BRAILLE WRITING THROUGH DIGITAL IMAGES (Modern American Journal of Engineering, Technology, and Innovation, 2025)
The article examines Braille automatic recognition technologies based on digital images. These technologies play an important role in creating equal access to information for persons with special needs. The study covers the processes of image processing, contour separation, point identification, and their adaptation to Braille characters. The effectiveness of using machine learning algorithms was also discussed. The results allow for the development of solutions that can be applied to education and everyday life in this area.